2019
DOI: 10.1128/aem.02271-18
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Cellular Evaluation of a Fluorine-Phosphorus-Doped Titanium Alloy, a Novel Antibacterial and Osteostimulatory Biomaterial with Potential Applications in Orthopedic Surgery

Abstract: Joint prosthesis failure is mainly related to aseptic loosening and prosthetic joint infections, both of which are associated with high morbidity and substantial costs for patients and health systems. The development of a biomaterial that is capable of stimulating bone growth while minimizing bacterial adhesion would reduce the incidence of prosthetic failure. We report antibacterial and osteostimulatory effects in a novel fluorine-phosphorus (F-P)-doped TiO2 oxide film grown on Ti-6Al-4V alloy with a nanostru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 96 publications
1
17
0
Order By: Relevance
“…The Ti–6Al–4V alloy is commonly used in orthopedic implants due to its favorable mechanical properties, corrosion resistance, and biocompatibility . We described the possibility of fabricating bottle‐shaped nanotubular oxide layers doped with fluorine (F) and phosphrous (P) by anodizing from Ti–6Al–4V to provide osseostimuling effect both in vitro and in vivo by avoiding aseptic loosening. Furthermore, these bottle‐shaped nanotubes can be loaded with drugs such as ibuprofen .…”
mentioning
confidence: 99%
“…The Ti–6Al–4V alloy is commonly used in orthopedic implants due to its favorable mechanical properties, corrosion resistance, and biocompatibility . We described the possibility of fabricating bottle‐shaped nanotubular oxide layers doped with fluorine (F) and phosphrous (P) by anodizing from Ti–6Al–4V to provide osseostimuling effect both in vitro and in vivo by avoiding aseptic loosening. Furthermore, these bottle‐shaped nanotubes can be loaded with drugs such as ibuprofen .…”
mentioning
confidence: 99%
“…This Al 3+ is not only the product of corrosion but also the result of the release of the cation retained inside the bottle-shaped nanotubes after the anodizing process. 19 The urine of P. aeruginosa -infected animals had lower Al levels than their noninfected counterparts. It had previously been shown that P. aeruginosa is capable of capturing a limited amount of Al released from bNT Ti-6Al-4V in vitro through an irreversible uptake mediated by pyochelin.…”
Section: Discussionmentioning
confidence: 94%
“…F- and P-doped bottle-shaped nanotubular (bNT) oxide layers of Ti-6Al-4V alloy 18 were obtained by the anodizing process and evaluated at microbiological and cellular levels. 19 Despite bNT layers releasing aluminum (Al) from the inside of the nanostructure and the resulting ions being captured by P. aeruginosa , this biomaterial is noncytotoxic and displays improved osteoblastic proliferation, mineralization, and differentiation in vitro. 19 Thus, the aim of this study was to evaluate the osseointegration of the F- and P-doped bottle-shaped nanostructured Ti-6Al-4V alloy and to monitor of urine aluminum concentration as a biomaterial marker of P. aeruginosa infection in Ti-6Al-4V implants in an in vivo rabbit model.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations